Shake hands with the devil : the failure of humanity in Rwanda - Dallaire, Roméo; Beardsley, Brent (Toronto : Random House, 2003)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: 1994.; burgeroorlogen; Rwanda